1986
DOI: 10.1111/j.1432-1033.1986.tb09574.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and reconstitution properties of human placental aromatase. A cytochrome P-450-type monooxygenase

Abstract: The hemoprotein component of human placental aromatase (estrogen synthetase) has been purified to a high degree of homogeneity by a combination of affinity and adsorption chromatography on aminohexyl-Sepharose, concanavalin-A-Sepharose, and hydroxyapatite. The monomeric form of the enzyme has an M , of 55000 +_ 1000 as estimated by sodium dodecyl sulfate gel electrophoresis. Its absolute spectrum shows a high-spin Soret band at 394 nm while its reduced, CO-difference spectrum has a maximum at 447 1 nm. Full re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…Thus, published findings have claimed that aromatization of 19-norandrogens is both possible [11][12][13][14] or not possible [7][8][9][10] using various in vitro systems including placental microsomes and granulosa or Leydig cells. Previous publications describing a variety of aromatase preparations and detection methods suggested that both MENT and 19-NT could be aromatized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, published findings have claimed that aromatization of 19-norandrogens is both possible [11][12][13][14] or not possible [7][8][9][10] using various in vitro systems including placental microsomes and granulosa or Leydig cells. Previous publications describing a variety of aromatase preparations and detection methods suggested that both MENT and 19-NT could be aromatized.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatization of C19 androgens such as T and androstenedione (AD) to their C18 aromatic A-ring products, estradiol and estrone (E 1 ), respectively, takes place in three sequential steps [4][5][6]: (1) hydroxylation of the C19-methyl group; (2) a second hydroxylation of the C19-methyl group to form a 19-oxo-compound; (3) cleavage of the bond between C10 and C19 to yield formic acid and the aromatized A-ring product with loss of the hydrogen atoms at the 1β and 2β positions. Although the mechanism of action of human aromatase involves the C19-methyl group, published findings concerning the potential aromatization of 19-norandrogens in vitro and in vivo have been contradictory [7][8][9][10][11][12][13][14]. Most of these studies have employed human placental microsomes or Leydig or granulosa cells which contain other enzymatic activities, and detection methods involving thin layer or gas chromatography, HPLC, or radioimmunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization and increased content caused by substrates or inhibitors has been found for many enzymes: for example, the cellular concentrations of arginase (Schimke 1964) and tryptophan pyrrolase (Schimke et al 1965) in rat liver are known to become increased as a result of decreased protein degradation dependent on the substrates, arginine and tryptophan. Furthermore, steroidogenic cytochrome P450 11β and aromatase were successfully purified in the presence of deoxycorticosterone (Takemori et al 1975) and testosterone (Harada 1988) or androstenedione (Tan & Muto 1986) used as substrate stabilizers to prevent inactivation of the enzyme. More recently, immunoreactive aromatase in the quail brain was found to be increased by the specific inhibitors, fadrozole and vorozole (Foidart et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Cyp19 encodes for a cytochrome P450 aromatase, an enzyme catalysing the conversion of androgens into oestrogens (Tan and Muto, 1986;Mendelson et al, 1990). Aromatase activity has been demonstrated in multiple tissues including normal and transformed breast tissues (James et al, 1987;Bulun and Simpson, 1994;Santen et al, 1994;Sasano et al, 1994).…”
mentioning
confidence: 99%